THE EFFECT OF FINANCIAL LITERACY, BUSINESS DURATION AND EDUCATION LEVEL ON FINANCIAL SUSTAINABILITY OF MSMES - Kennedy Kennedy; Hery Heryanto; Arienda Gitty Ramadani (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study aims to analyze how financial literacy business duration and background education affects the financial sustainability of msmes in Batam. Researcher used a quantitative approach with a survey method through questionnaires distributed to 384 msmes owners as a sample, which were selected using purposive sampling technique. The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the validity, reliability and relationships among the variables. Based on survey data from 384 MSME owners in Batam, results show that financial literacy has a significant positive impact indicating that owners with strong understanding of financial principles are better equipped to maintain and enhance the financial health of the business. Moreover, business duration also contributes positively suggesting that experience over time contributes to financial resilience, while education levels are surprisingly associated with slightly lower financial sustainability, implying that formal education may not directly translate into practical skills needed for msmes sustainability. This study concludes that financial literacy is the most dominant factor influencing financial sustainability, while business duration and education contribute to a lesser extent.